Akibat Hukum Perbuatan Pendiri yang Tidak Merealisasikan Setoran Modal pada Perseroan Terbatas - Shawina Widyandarie; Hasim Purba; Mahmul Siregar (CV Rewang Rencang, 2025)
Founders who fail to make capital contributions to limited liability companies create legal uncertainty because valid legal entity status requires proof of capital deposits. This research employs normative juridical methodology with statutory and library research approaches. The study concludes that founders must fulfill capital contribution obligations after company establishment to ensure legal certainty. Legal consequences of non-contribution constitute unlawful acts resulting in suspended shareholder rights and joint liability for damages. Founders must fulfill capital contribution responsibilities so that corporate organs can perform legal acts with legal certainty in company management.